THE EVALUATION OF THE TUNNELING MAGNETORESISTANCE MANGANITE- PMMA COMPOSITES - A.V. Vasiliev; A.A. Eliseev; E.O. Anohin; L.A. Trusov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2013)
Lanthanum-strontium manganite containing composites were synthesized by a warm pressing technique. The LSMO precursor was prepared by modified sol-gel method. Samples showed two types of magnetoresistance effect, tunnel, due to composite structure, and colossal, due to LSMO properties.